Inhibition of the ATP synthase sensitizes Staphylococcus aureus towards human antimicrobial peptides - Liping Liu (Nature Portfolio, 2020)
Abstract Antimicrobial peptides (AMPs) are an important part of the human innate immune system for protection against bacterial infections, however the AMPs display varying degrees of activity against Staphylococcus aureus. Previously, we showed that inactivation of the ATP synthase sensitizes S. aureus towards the AMP antibiotic class of polymyxins. Here we wondered if the ATP synthase similarly is needed for tolerance towards various human AMPs, including human β-defensins (hBD1-4), LL-37 and histatin 5. Importantly, we find that the ATP synthase mutant (atpA) is more susceptible to killing by hBD4, hBD2, LL-37 and histatin 5 than wild type cells, while no changes in susceptibility was detected for hBD3 and hBD1. Administration of the ATP synthase inhibitor, resveratrol, sensitizes S. aureus towards hBD4-mediated killing. Neutrophils rely on AMPs and reactive oxygen molecules to eliminate bacteria and the atpA mutant is more susceptible to killing by neutrophils than the WT, even when the oxidative burst is inhibited.These results show that the staphylococcal ATP synthase enhance tolerance of S. aureus towards some human AMPs and this indicates that inhibition of the ATP synthase may be explored as a new therapeutic strategy that sensitizes S. aureus to naturally occurring AMPs of the innate immune system.